A CRISPR-Cas9 system protecting E. coli against acquisition of antibiotic resistance genes - Danna Lee; Petra Muir; Sara Lundberg; August Lundholm; Linus Sandegren; Sanna Koskiniemi (Scientific Reports)
Abstract Antimicrobial resistance (AMR) is an increasing problem worldwide, and new treatment options for bacterial infections are direly needed. Engineered probiotics show strong potential in treating or preventing bacterial infections. However, one concern with the use of live bacteria is the risk of the bacteria acquiring genes encoding for AMR or virulence factors through horizontal gene transfer (HGT), and the transformation of the probiotic into a superbug. Therefore, we developed an engineered CRISPR-Cas9 system that protects bacteria from horizontal gene transfer. We synthesized a CRISPR locus targeting eight AMR genes and cloned this with the Cas9 and transacting tracrRNA on a medium copy plasmid. We next evaluated the efficiency of the system to block HGT through transformation, transduction, and conjugation. Our results show that expression of the CRISPR-Cas9 system successfully protects E. coli MG1655 from acquiring the targeted resistance genes by transformation or transduction with 2–3 logs of protection depending on the system for transfer and the target gene. Furthermore, we show that the system blocks conjugation of a set of clinical plasmids, and that the system is also able to protect the probiotic bacterium E. coli Nissle 1917 from acquiring AMR genes.